Use of fluoroscopic-guided transsacral block for the treatment of iatrogenic post-injection sciatic neuropathy: Report of three cases - GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2019)
Post-injection sciatic neuropathy (PISN) from an inadvertent intramuscular injection in the gluteal region is a type of iatrogenic sciatic nerve injury. Patients with neuropathic pain following PISN frequently experience disability leading to restrictions in daily activities and pain, which may be resistant to conventional treatments and physiotherapy in some cases. To date, minimal invasive procedures for neuropathic pain have been performed with various medications at the site of lesion. Herein, we report three adult male cases with PISN-associated neuropathic pain who were resistant to conservative management and were treated with fluoroscopy-guided transsacral block.
Keywords: Epidural; fluoroscopy; injections; intractable; methylprednisolone; pain; sciatic neuropathy; DORSAL-ROOT GANGLIA; NERVE INJURIES; SPINAL-CORD; PAIN; METHYLPREDNISOLONE; EXPERIENCE; MANAGEMENT